Penerapan Kebijakan Pembelajaran di MDTA Al – Khairat - Adilla Aisyahrani; Nurul Bayani (Education : Jurnal Sosial Humaniora dan Pendidikan, 2024)
Education is a very important issue for determining the turn of events and indications of people, and for the existence of a country. Understanding the importance of the training section as a key driver for a country's progress, public authorities consistently strive to accomplish changes in the school sector, especially those identified with teaching faculties, financing, frameworks, educational programs, This research aims to describe the Learning policies implemented by MDTA AL Khairat Tembung. However, the researchers here are more focused on discussing the learning carried out by MDTA Al Khairat, the way teachers manage the class, the innovations made so that the class is not boring, and the steps taken by MDTA to make it more advanced and developed. This research uses a qualitative method, descriptive research type. Data was obtained through observation, interviews and documentation techniques with a focus on data on the implementation of learning policies at MDTA Al Khairat. The results of the research are that the implementation of the learning system at the MDTA (Madrasah Diniyah Takmiliyah Awaliyah) education level is very important in ensuring that students receive quality education that suits their needs. In implementing a learning system, several things that need to be considered are curriculum adjustments, use of effective learning methods, use of technology, and involvement of parents and the community.